Sistem Pakar Mendiagnosa Penyakit Idiopathic Thrombocytopenic Purpura (ITP) Menerapkan Hybrid Case Based Dengan Metode Cosine Similarity - Idris, Agita Sari (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2024)
Idiopathic Thrombocytopenic Purpura (ITP) is an autoimmune disease that attacks blood platelets (platelets) so that the number of red blood cells (thrombocytes) is reduced. This disease is an abnormality in blood clotting cells, namely platelets, whose number decreases, causing bleeding. Bleeding that occurs generally on the skin is in the form of red spots to bluish rashes. Until now the main cause of this disease is not known for certain, but it usually occurs after a viral infection. Meanwhile, in adults, ITP is usually a chronic or long-term disorder. In order to avoid disease conditions caused by ITP, treatment and knowledge are needed so that it is not too late to take action so that the disease does not become serious. Therefore, we need an expert system that is able to carry out temporary diagnoses without using large costs, namely an expert system. The expert system created applies Hybrid Case Based with the Cosine Similarity method. This method is a combination of systems, namely Rule Based Reasoning (RBR) and Case Based Reasoning (CBR), this method has better accuracy than the method that runs alone. This method will process a symptom so that the disease the patient is suffering from can be detected. This expert system can be accessed anywhere and at any time, making it very easy for someone to diagnose the disease they are suffering from. The implementation of this expert system will use the Microsoft Visual Basic 2008 programming language.